Metformin Improves Fertility in Women with Polycystic Ovary Syndrome (PCOS): A Systematic Review - Aidil Akbar (Buletin Farmatera, 2023)
Abstract: Polycystic ovary syndrome (PCOS) Causes 6-15% of female infertility, of which 80% is characterized by the occurrence of hyperinsulinemia resulting in impaired endometrial function. Metformin therapy in improving insulin sensitivity has been widely reported, but investigations are needed to determine the characteristics of metformin therapy research in PCOS cases with a literature review study approach. In the collection of systematic studies, Publish and Perish, Mendeley and Microsoft Excel applications, using the keyword metformin improves fertility in women with PCOS. From 500 articles collected, 16 articles were included in the inclusion criteria, and it was found that many studies had been conducted in several countries (Iran, India, USA, Italy, Egypt, Pakistan and Saudi Arabia involving 2295 subjects, with a dose range of 500 mg to 2000 mg, with a duration of administration of 14 days to 9 months. In this study, it was concluded that metformin intervention studies both singly and in combination clinically have been conducted in several countries where most studies show that metformin can improve clinical and laboratory improvements in PCOS patients, which can improve the fertility rate of women with PCOS.